Valorization of sawdust by co-composting with food waste using a small-scale composter - Hadi Bello; Akeem Jimoh (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study aimed to produce a value-added product by co-composting sawdust with food waste using a small-scale composter.Method The composting experiment was carried out using 60L composting bins with a hole of 3 mm and 10 cm apart drilled on its side. Three experimental trials 1, 2 and 3 were adopted in this study with mixture of sawdust and food waste (Trial 1= 80% sawdust + 20% food waste, Trial 2 = 70% sawdust + 30% food waste, Trial 3 = 60% sawdust + 40% food waste). The composting process lasted for 90 days. Parameters examined throughout the composting process include temperature, moisture content, pH, electrical conductivity, organic matter content, and organic matter losses.Results The results indicated that all the compost trials exhibit good development of composting process, with the highest solid organic degradation reached in a shorter period in compost trial 3. The temperature profile of the three trials are the same and above 60 0C after 30 days of composting. The compost samples had a pH ranging from 5.9 to 9.4. The electrical conductivity of the three composting trials was following the recommended value. The best compost trial that produces quality compost is compost trial 3.Conclusion The results showed that all composts obtained were stable and matured. In brief, recycling sawdust through the composting process to obtain valuable end products is adequate but in the presence of nitrogen-rich waste, such as waste food materials.